Pädagogik und Geschlechterverhältnisse in der Pandemie Analyse und Kritik fragwürdiger Normalitäten - Langer, Antje Prof. Dr; Mahs, Claudia Dr; Thon, Christine Prof. Dr; Windheuser, Jeannette Prof. Dr; Kleinau, Elke Prof. Dr; Glammeier, Sandra Prof. Dr; Kampshoff, Marita Prof. Dr; Boger, Mai-Anh Dr. phil; Bergold-Caldwell, Denise Dr; Grenz, Frauke; Günster, Anne; Baar, Robert Prof. Dr; et al. (Schriftenreihe der Sektion Frauen- und Geschlechterforschung in der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2022)
During the Corona pandemic, many topics became the subject of public debates that have long preoccupied educational science in general and women's and gender studies in particular: Reproduction of social inequality in educational contexts, unequal distribution of care work, marginalization of non-heteronormative lifestyles, and many more. In the pandemic, the struggle for a return to "normality" is omnipresent. The contributions to this volume show, from the perspectives of gender theory and educational science, that this normality is part of the conditions of the crisis itself and that a return to such normality would perpetuate existing relations of power.